Efektivitas Penggunaan Media Edukasi Gizi terhadap Pengetahuan dan Sikap Hipertensi pada Penderita Hipertensi : Literature Review - Rosita Elsa Monica; Ratih Kurniasari (Universitas Airlangga, 2026)
Background: In Indonesia, the number of patients with hypertension continues to increase annually, with a prevalence of 30.8% according to the 2023 Indonesian Health Survey (Survey Kesehatan Indonesia or SKI). A lack of knowledge means that many patients do not understand the definition, causes, healthy dietary patterns, or potential complications of hypertension. Therefore, nutrition education through communication, information, and education (Komunikasi, Informasi, dan Edukasi or KIE) media should be utilized to improve the knowledge of hypertensive patients. Objectives: This study aims to identify the impact of nutrition education using KIE media on hypertensive patients’ knowledge. Methods: Secondary data were obtained by searching scientific articles in the Google Scholar database published within the last ten years (2015–2025). After screening, eight articles met the inclusion criteria and were included in this review. Results: KIE media on nutrition enhance hypertensive patients' understanding and ability to implement nutritional recommendations by providing accessible and engaging formats, including clear text, audio, visuals, and media such as posters, audiovisual materials, podcasts, leaflets, and blogs. Conclusion: Nutrition education using KIE media is effective in improving hypertensive patients’ knowledge regarding hypertension.